Perancangan Sistem Closure pada Adaptive Clothing untuk Orang dengan Demensia (ODD) Tahap Moderate - Putri Rizky Salsabila; Tyar Ratuannisa (Jurnal Sosioteknologi, 2023)
Adaptive clothing is one of the media to optimize the living conditions of people with dementia (PwD), which can solve the problem of undressing in social situations, is friendly for caregivers, and is suitable for the physical and psychological conditions of PwD. The method used is qualitative with a comparative approach by researching closure systems for adaptive clothing in the online market. This research produces design recommendations based on the type, development, and comparison of closure systems on adaptive clothing on the market. Adaptive clothing products are expected to stimulate or train memory, reduce anxiety, improve quality of life, and facilitate caregivers in caregiving.